Creation of the tourism cluster as a way to economic grows of the region - Данько, Наталія (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
The goal of the article is to consider creating a tourism cluster as a basis for economic growth of the region. Analyzing, systemizing, generalizing scientific works of a number of scientists, the auyhor considers features of creation of cluster associations in the sphere of tourism, their distinction from the associations (networks) of enterprises and impact on investment attractiveness of the region. The study specifies the tourism cluster concept and studies the most successful experience of creation of tourism cluster at the cross–section of various industries: California wine cluster, Tropical Northern Queensland cluster and South–African tourism cluster. The author comes to conclusion that experience of creating tourist clusters in former industrial region is useful for the Kharkiv region: Ruhr Valley, Glasgow etc. – in accordance with the «Creative economy: expansion of ways of local development» concept, proposed by UNESCO. The article offers the procedure of creating a tourism cluster and managing its development using method that take into account different stages of development evolution of clusters. The prospects for further studies are coordination of the methods of creation and management of cluster ICM333 with specific features of the tourist industry and Ukrainian legislation.